The fracture mechanism of cotton stalks through FDEM analysis - Xirui Yang; Peiyu Chen; Yongcheng Zhang; Yong Zeng; Haipeng Lan; Yurong Tang (Biosystems Engineering, 2026)

Placental transfer efficiencies of multiple metals: Patterns, and influence factors - Yu Li; Xianglian Peng; Nian Liu; Hua Guo; Yurong Jia; Wenjing Li; Ziyin Liang; Po Tang; Guohuan Zhang; Qinfei Zhou; Yong Liang; Ligang Hu; et al. (Journal of Environmental Sciences, 2026)

Effects of Fermented Mulberry Leaf Powder on Growth Performance, Meat Quality, Antioxidant Capacity, and Fat Metabolism in Grass Carp (Ctenopharyngodon idellus) - Hongquan Wang; Shuang Wu; Xiwen Zhang; Wei Tang; Xiangyue Zou; Yurong Zhao (Fishes, 2026)
The use of plant-based fermentation products as substitutes for costly feed ingredients like fishmeal and soybean meal has been at the forefront of aquaculture research. This study investigated the effects of dietary fermented mulberry leaf powder (FMLP) on grass carp (0.86 ± 0.07 kg). Fish were fed a basal diet supplemented with 0%, 5%, 10%, or 15% FMLP for 70 days to assess impacts on growth, muscle quality, antioxidant status, and lipid metabolism. Results indicated that FMLP did not significantly affect growth performance (p > 0.05). However, it reduced the hepatosomatic index, viscerosomatic index, condition factor, and intraperitoneal fat ratio (p

Amorphous PdSe ultrafine nanoparticles boosts ethanol electrooxidation via dual-pathway mechanism - Zhihan Liu; Shiguo Yan; Qin Luo; Yifan Cao; Yurong Fu; Huanyue Zhang; Yiyang Wang; Xiaodi Tang; Yong Yi; Cuilan Tang (Chemical Engineering Journal, 2026)

Viral isolation and genomic characteristics of the first bovine parainfluenza virus type 3 isolated from water buffaloes (Bubalus bubalis) in China - Can Bao; Yunxin Ren; Cheng Tang; Yurong Su; Hua Yue; Xi Chen (The Veterinary Journal, 2026)

Identify and Suppress Magnetotelluric Data using Long Short-Term Memory, Multi-Head Attention and ResNet - Yi Tang; Tianjun Cheng; Lei Zhou; Xingbing Xie; Yurong Mao; Liangjun Yan (Pure and Applied Geophysics, 2026)

Soil Fungi Composition and Functional Groups in Phosphate Mine Spontaneous Recovery Areas: A Combined High‐Throughput and Traditional Approaches - Yongsheng Peng; ChengJiao Dao; YuRong Wang; Rong Tang; Neelamanie Yapa; Garumuni Dilrukshi Nadeeshani Menike; Anuruddha Karunarathna; Abdallah M. Elgorban; Alanoud T. Alfagham; Saowaluck Tibpromma; Y. A. P. K. Dayasena; Kai Yan (New Zealand Journal of Botany, 2026)
Our study on the composition and functional groups of soil fungi in phosphate mine spontaneous recovery areas has identified several fungal genera that play a crucial role in soil regeneration. This finding carries significant practical implications for the methodologies employed in mine site reclamation. We used amplicon sequencing‐based high‐throughput sequencing (HTS) and traditional fungal culturing methods in the Kunyang phosphate mining area of Kunming City, Yunnan Province, China, to comprehensively assess fungal community composition and functional diversity during spontaneous regeneration. The fungal communities in the natural recovery area differ significantly from those in the abandoned mining area, exhibiting notably higher fungal diversity indices and a more complex co‐occurrence pattern. Through HTS, 13 fungal phyla and 447 fungal genera were identified. Among them, Ascomycota is the dominant phylum, followed by Basidiomycota , and Mortierella was the primary genus. All cultured fungi belong to Ascomycota , comprising 16 genera, among which Purpureocillium and Penicillium are predominant. The majority of cultured fungi belong to pathogenic and saprophytic groups, while Mortierella is the only potential symbiotic genus. Notably, six fungal genera were identified exclusively through culturable approaches: Aureobasidium , Cladosporium , Cytospora , Discohainesia , Neopyrenochaeta , and Saccharomyces . These genera play a crucial role in soil regeneration, and their identification is a significant step toward understanding their functional characteristics. The results indicate that rhizosphere fungal communities vary significantly under distinct restoration strategies. This underscores the importance of considering regional specificity, such as local climate and soil conditions, when harnessing fungi for vegetation rehabilitation. The synergistic application of high‐throughput sequencing alongside culturable methods is not only beneficial but also crucial for the efficient screening and utilization of functional fungi. This integration reassures professionals in the field about the effectiveness and reliability of their research methods, thereby enhancing their confidence in the outcomes.

Green photocatalytic conversion of CO2 to renewable fuel over Ag/Cu-TiO2/g-PAN nanofibers under solar irradiation - Shanshan Sun; Yurong He; Tianqi Tang; Siyu Hui (Journal of Cleaner Production, 2026)

A major qualitative trait locus increases antioxidant activity in testaless peanut seeds - Xing Zhao; Yurong Li; Xiaodong Tang; Sijie Liu; Qiao Su; Pengju Hu; Xinxin Jin; Yahui Song; Jin Wang; Yongqing Yang (Theoretical and Applied Genetics, 2026)

Caged broiler aggregation behavior recognition via target detection and label merging - Chao Yuan; Zikang Chen; Yurong Tang; Ruqian Zhao; Longshen Liu; Mingxia Shen (Computers and Electronics in Agriculture, 2025)

Developed DNS-DEM coupling model for normal collisions of ellipsoidal particles on wet surfaces - Zhichao Song; Yurong He; Jingda Xia; Tianqi Tang (Chemical Engineering Journal, 2025)

A 5-year field study to assess interannual variability and determinants of cotton fiber quality in intercropping systems - Haoyue Qin; Yurui Tang; Xin Li; Yurong Qiu; Jian Wang; Yingchun Han; Guoping Wang; Shiwu Xiong; Minghua Xin; Wenli Du; Lu Feng; Yongjiang Zhang; et al. (European Journal of Agronomy, 2025)

The double-edged sword effect of sulfate: enhanced stress tolerance but increased arsenic accumulation in rice grains - Yuepeng YIN; Min NIE; Yurong WANG; Liqin HE; Xin TANG; Zhigao ZHOU; Taolin ZHANG; Xingxiang WANG (Pedosphere, 2025)

Rapid Identification of Soybean SC15 Resistance Locus to Soybean Mosaic Virus by BSA-seq - Xiangmin Tang; Gang Jin; Huaizhu Chen; Zhaoyan Cai; Zhenguang Lai; Qingyuan Wei; Kai Li; Haijian Zhi; Yurong Tan; Dongliang Chen; Weiying Zeng; Shouzhen Yang (Plant Molecular Biology Reporter, 2025)

Why do rice farmers reuse pesticides after purchasing regional pest control services? - Lin Tang; Xiaofeng Luo; Sanxia Du; Yanzhong Huang; Yurong Yang (Environment, Development and Sustainability, 2025)

Research on intercropping from 1995 to 2021: a worldwide bibliographic review - Yurui Tang; Yurong Qiu; Yabing Li; Huasen Xu; Xiao-Fei Li (Plant and Soil, 2025)

Reducing cadmium and arsenic accumulation in rice grains: The coupled effect of sulfur's biomass dilution and soil immobilization analyzed using meta-analysis and machine learning - Yuepeng Yin; Changfeng Ding; Xin Tang; Zhigao Zhou; Min Nie; Yuan Yuan; Yifan Qian; Liqin He; Ziyao Li; Zhihong Guo; Lirong Li; Qing Zhao; et al. (Science of The Total Environment, 2024)

Structurally programmed bioderived polyimide for foldable humidity sensors with ultrafast response and recovery times - Caihong Gong; Huilong Liu; Shaoji Wu; Zhao Liu; Sutong Zheng; Yanhuang Tang; Zhiming Qiu; Rui Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

Corrigendum to “Selective and efficient immobilization of cadmium in soil by layered double hydroxides intercalated with the mercaptosuccinic acid” [Sci. Total Environ. volume 937, 10 August 2024, 173473] - Liqin He; Yurong Wang; Changfeng Ding; Gaoxiang Huang; Xiangming Tu; Zhigao Zhou; Yuepeng Yin; Xin Tang; Zhihong Guo; Ziyao Li; Taolin Zhang; Xingxiang Wang; et al. (Science of The Total Environment, 2024)

GDNF's Role in Mitigating Intestinal Reactive Gliosis and Inflammation to Improve Constipation and Depressive Behavior in Rats with Parkinson’s disease - Qin Xiaoling; Guo Yurong; Xue Ke; Qiu Yuxiang; An Panpan; Du Yinzhen; Li Xue; Liu Tingting; Tang Chuanxi (Journal of Molecular Neuroscience, 2024)

Selective and efficient immobilization of cadmium in soil by layered double hydroxides intercalated with the mercaptosuccinic acid - Liqin He; Yurong Wang; Changfeng Ding; Gaoxiang Huang; Xiangming Tu; Zhigao Zhou; Yuepeng Yin; Xin Tang; Zhihong Guo; Ziyao Li; Taolin Zhang; Xingxiang Wang; et al. (Science of The Total Environment, 2024)

Cadmium found in peanut (Arachis hypogaea L.) kernels mainly originates from root uptake rather than shell absorption from soil - Xin TANG; Yurong WANG; Changfeng DING; Yuepeng YIN; Zhigao ZHOU; Taolin ZHANG; Xingxiang WANG (Pedosphere, 2024)

Surface adsorbed–H2O promoted aerobic oxidation of biomass–derived alcohols on MnOx catalysts - Yurong Zhang; Junpeng Wang; Meiying Niu; Jun Tang; Zhipeng Chen; Chao Wan; Qingping Ke (Chemical Engineering Journal, 2024)

Increased overyielding probability and yield stability from a 5-year cotton-based intercropping - Yurui Tang; Yurong Qiu; Xin Li; Haoyue Qin; Jian Wang; Shijie Zhang; Yingchun Han; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Shiwu Xiong; et al. (European Journal of Agronomy, 2024)

Impact of iron and sulfur cycling on the bioavailability of cadmium and arsenic in co-contaminated paddy soil - Yuepeng Yin; Yurong Wang; Changfeng Ding; Zhigao Zhou; Xin Tang; Liqin He; Ziyao Li; Taolin Zhang; Xingxiang Wang (Journal of Hazardous Materials, 2024)

A Chinese longitudinal maternity cohort study (2013–2021) on intrahepatic cholestasis phenotypes: Risk associations from environmental exposure to adverse pregnancy outcomes - Haitong Zhe Sun; Haiyang Tang; Jing Fang; Haizhen Dai; Huan Zhao; Siyuan Xu; Qingyi Xiang; Yijia Tian; Yurong Jiao; Ting Luo; Meishuang Huang; Jia Shu; et al. (Journal of Hazardous Materials, 2024)

Achieving high-rate and long-life Zn metal anodes via constructing interfacial gradient heterostructure - Yilun Ren; Biao Wang; Shaozhong Chang; Hao Wu; Yujie Ma; Fengqi Li; Cong Wang; Jian Gu; Yurong Yang; Shaochun Tang; Xiangkang Meng (Chemical Engineering Journal, 2024)

Prediction of the non-uniform drying of wet grain in a fluidised-bed based on a modified CFD-DEM drying model - Hanru Liu; Yurong He; Tianqi Tang; Ming Zhai (Biosystems Engineering, 2023)

Driven by utility or regret? Investigating the influence of decision-rule heterogeneity on public preferences for desertification control policies - Yong Zeng; Biqi Mao; Yurou Zhang; Yurong Tang (Journal of Cleaner Production, 2023)

Directly linking plant N, P and K nutrition to biomass production in cotton-based intercropping systems - Yurong Qiu; Xin Li; Yurui Tang; Shiwu Xiong; Yingchun Han; Zhanbiao Wang; Lu Feng; Guoping Wang; Beifang Yang; Yaping Lei; Wenli Du; Xiaoyu Zhi; et al. (European Journal of Agronomy, 2023)

Particle coating growth behaviors in a spray fluidized bed based on Gas-Liquid-Solid Quasi-Three-phase DEM numerical simulation - Aiming Deng; Tianqi Tang; Shanshan Sun; Yurong He (Chemical Engineering Journal, 2023)

A core-molecule-shell Au@PATP@Ag nanorod for nicotine detection based on surface-enhanced Raman scattering technology - Yuhui Chen; Yunfei Tang; Peng Li; Yong Wang; Yurong Zhuang; Shihao Sun; Dingzhong Wang; Wei Wei (Analytica Chimica Acta, 2023)

Fast and efficient methane storage in massive fibrous hydrates produced via pre-frozen activated carbon - Yongji Wu; Yurong He; Ming Zhai; Tianqi Tang (Chemical Engineering Journal, 2023)

Interpreting the nonstationary relationship between El Niño–Southern Oscillation and the winter precipitation over southeast China - Wenqian Tang; Xin Geng; Yan Zhao; Yurong Gao; Yiwan Huang; Shuchang Ning (International Journal of Climatology, 2022)
The amount of winter precipitation over southeast China (SCWP) is significantly affected by the El Niño–Southern Oscillation (ENSO), with generally an enhanced SCWP response to El Niño events. In this paper, we find that this relationship shows remarkable nonstationarities on the multidecadal timescale. Running ENSO–SCWP correlation maintains statistically significant before the mid‐1960s and after the mid‐1990s but not during the interim period, which exhibits an approximate synchronized temporal evolution with the Atlantic Multidecadal Oscillation (AMO). A statistical method for interpreting nonstationary relationships is then applied to quantitatively verify and measure this possible AMO modulation. It is demonstrated that the nonstationary ENSO–SCWP correlation can be expressed to a large extent by the influence of the AMO–ENSO nonlinear effect (AMO*Niño3.4) on the SCWP. This influence intensifies the ENSO–SCWP relationship during the positive AMO phase but weakens it during the negative AMO phase. Therefore, the nonstationarity in the ENSO–SCWP relationship comes predominantly from an AMO modulation via this key nonlinear effect. We further suggest that a positive AMO favours a westward shift of ENSO sea surface temperature (SST) anomaly pattern in the tropical Pacific. Correspondingly, the anomalous western North Pacific (WNP) anticyclone also migrates westward, which gives rise to pronounced moisture transports and vertical motions over the adjacent southeast China, thereby resulting in a significant ENSO–SCWP relationship. In contrast, during the negative AMO phase, the eastward‐shifted ENSO SST and WNP anticyclonic anomalies produce significant atmospheric anomalies primarily to the east of the Chinese mainland, thus having less effect on the SCWP.

Heavy metal domestication enhances beneficial effects of arbuscular mycorrhizal fungi on lead (Pb) phytoremediation efficiency of Bidens parviflora through improving plant growth and root Pb accumulation - Yurong Yang; Beitong Huang; Jiazheng Xu; Zhenxin Li; Zhanhui Tang; Xuefeng Wu (Environmental Science and Pollution Research, 2022)

Interactive effects of exogenous melatonin and Rhizophagus intraradices on saline-alkaline stress tolerance in Leymus chinensis - Yurong Yang; Yaping Cao; Zhenxin Li; Anastasiia Zhukova; Songtao Yang; Jinlong Wang; Zhanhui Tang; Yonghong Cao; Yifei Zhang; Deli Wang (Mycorrhiza, 2020)

Preferential insertion of a Ty1 LTR-retrotransposon into the A sub-genome’s HD1 gene significantly correlated with the reduction in stem trichomes of tetraploid cotton - Mengling Tang; Xingcheng Wu; Yuefen Cao; Yuan Qin; Mingquan Ding; Yurong Jiang; Chengdong Sun; Hua Zhang; Andrew H. Paterson; Junkang Rong (Molecular Genetics and Genomics, 2020)

Assessment of arbuscular mycorrhizal fungi status and heavy metal accumulation characteristics of tree species in a lead–zinc mine area: potential applications for phytoremediation - Yurong Yang; Yan Liang; Amit Ghosh; Yingying Song; Hui Chen; Ming Tang (Environmental Science and Pollution Research, 2015)

Arbuscular Mycorrhizal Fungi Alter Fractal Dimension Characteristics of Robinia pseudoacacia L. Seedlings Through Regulating Plant Growth, Leaf Water Status, Photosynthesis, and Nutrient Concentration Under Drought Stress - Yurong Yang; Ming Tang; Ronan Sulpice; Hui Chen; Shuai Tian; Yihui Ban (Journal of Plant Growth Regulation, 2014)